The association between serum angiogenin and osteopontin levels and coronary collateral circulation in patients with chronic total occlusion - Gürses, Kadri Murat (Anatol J Cardiol, 2019)
OBJECTIVE: A well-developed coronary collateral circulation lowers both in-hospital and long-term morbidity and mortality limiting the infarct. Angiogenin (AGN) and osteopontin (OPN) are known to be potent inducers of angiogenesis. The aim of the present study was to investigate the relationship between serum ANG and OPN levels and collateral filling grade in subjects with stable coronary artery disease (SCAD). METHODS: A total of 122 age- and gender-matched consecutive patients who were found to have total occlusion (n=70) and no significant stenosis in epicardial coronary arteries (n=52) who underwent coronary angiography due to SCAD between January 2015 and July 2017 were included in the study. AGN and OPN levels were measured using enzyme-linked immunosorbent assay. Coronary collateral circulation was graded using Rentrop’s classification of collateral filling. RESULTS: A total of 52 patients (61.60±11.78 years, 61.5% male) without significant epicardial coronary artery stenosis and 70 patients (62.87±8.24 years, 65.7% male) with totally occluded coronary arteries were included in the study. Subjects with total occlusion had significantly higher levels of AGN [122.00 (79.00–623.00) pg/mL vs. 98.00 (18.00–160.00) pg/mL, p<0.001] and OPN [1863.50 (125.00–6500.00) pg/mL vs. 451.00 (112.00–1850.00) pg/mL, p<0.001] than those without significant stenosis. In addition, AGN [127.00 (87.00–623.00) pg/mL vs. 110.00 (79.00–188.00) pg/mL, p=0.011] and OPN [2681.00 (126.00–6500.00) pg/mL vs. 649.00 (125.00–4255.00) pg/mL, p=0.001] levels were significantly higher in patients with better developed collaterals. Serum AGN and OPN levels were found to be significantly associated with coronary collateral development. CONCLUSION: AGN and OPN are associated with better developed coronary collateral circulation and may have therapeutic implications for the promotion of coronary collateral development.